2016
DOI: 10.1021/acsenergylett.6b00661
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven Water Splitting by a Covalently Linked Ruthenium-Based Chromophore–Catalyst Assembly

Abstract: The preparation and characterization of new Ru­(II) polypyridyl-based chromophore–catalyst assemblies, [(4,4′-PO3H2-bpy)2Ru­(4-Mebpy-4′-epic)­Ru­(bda)­(pic)]2+ (1, bpy = 2,2′-bipyridine; 4-Mebpy-4′-epic = 4-(4-methylbipyridin-4′-yl-ethyl)-pyridine; bda = 2,2′-bipyridine-6,6′-dicarboxylate; pic = 4-picoline), and [(bpy)2Ru­(4-Mebpy-4′-epic)­Ru­(bda)­(pic)]2+ (1′) are described, as is the application of 1 in a dye-sensitized photoelectrosynthesis cell (DSPEC) for solar water splitting. On SnO2/TiO2 core–shell el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 38 publications
2
71
0
Order By: Relevance
“…[2][3][4][5] Several Ru(II) based PS-WOC dyad assemblies have recently been coated on TiO 2 to build dyesensitized DSPECs with promising faradaic efficiencies for O 2 evolution. 6,7 The catalytic efficiency of dyad systems was investigated in a homogeneous system as well. In a study by Thummel et al, a Ru-Ru dyad assembly showed a TON of 134 under 6 h illumination, which is much higher than its analogous intermolecular system with a TON of 6.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Several Ru(II) based PS-WOC dyad assemblies have recently been coated on TiO 2 to build dyesensitized DSPECs with promising faradaic efficiencies for O 2 evolution. 6,7 The catalytic efficiency of dyad systems was investigated in a homogeneous system as well. In a study by Thummel et al, a Ru-Ru dyad assembly showed a TON of 134 under 6 h illumination, which is much higher than its analogous intermolecular system with a TON of 6.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Of these,d ye-sensitized photoelectrochemical cells (DS-PECs) utilize covalently coordinated chromophore-water oxidation catalyst (WOC) dyad assemblies [4][5][6] in an effort to mimic natural photosynthesis. [10][11][12][13][14][15][16][17][18][19] Although the use of robust heterogeneous assemblies such as oxides could be apromising solution to improve stability,the lack of complete control on the coordination of metal ions in oxide chemistry does not allow the preparation of oxidebased dyads. [7][8][9] Molecular ruthenium complexes (as photosensitizers and/or WOCs) remain the most widely used despite their high cost and easy decomposition under photocatalytic conditions.…”
mentioning
confidence: 99%
“…Photoelectrochemical Water Oxidation. Water oxidation was explored in core/shell nanoparticle SnO 2 /TiO 2 films with the core/shell structure assisting electron-hole separation at the SnO 2 /TiO 2 interface (25)(26)(27)(28)(29). Surface-loaded versions of related assemblies were investigated previously (30).…”
Section: Resultsmentioning
confidence: 99%